Vitamin B12 deficiency masquerading Addison’s disease: a case report of an adolescent male - M., Sudhaa Mani; S., Yasmeen Ahamed; Giri, Nanitha Lakshmi Kavitha; A., Jesudasan (International Journal of Research in Medical Sciences, 2020)
Intraoral pigmentations range from innocuous physiologic pigments to life-threatening malignant conditions. It is at the discretion of the observing clinician to identify the abnormal clinical manifestations and provide necessary intervention. There are controversies about delineating the definite etiology of the pigmentation such as race, exposure to ultra-violet radiation, drug-induced pigmentation post-inflammatory pigments of the oral cavity.